EVALUATION OF TRACKING SYSTEM PERFORMANCE BY RADIO FREQUENCY INSTALLED IN PREFERENCE CHAMBER - Maia, A.P.; Moura, D.J.; Massari, J.M.; Green, A.R.; Sarubbi, J.; Ferreira, R. (Revista Brasileira de Engenharia de Biossistemas, 2015)
Animal tracking systems throughout the production chain are increasing. Thus, every step of the production process can be monitored by means of intelligent systems that support accurate decision-making, maximizing the entire system. The objective of this study was to evaluate the performance of the electronic identification system by radio frequency (RFID) installed in an environmental preference chamber (CPA) throughout the detection of broiler movements, and was conducted in two parts: 1) Detection of the antennas range using a robot; 2) Tracking the movement of broilers between the compartments of the CPA. It was observed that the signal emitted by the RFID tag can be read approximately 10 cm away from the antenna, identifying an area of non-detection. Therefore, the RFID system installed in the CPA did not provide the expected performance, and this technology should be redesigned or replaced.